2018
DOI: 10.1177/2156869318813006
|View full text |Cite
|
Sign up to set email alerts
|

Spillover and Crossover Effects of Work-Family Conflict among Married and Cohabiting Couples

Abstract: The present study uses Wave 8 of the German Family Panel to test the spillover and crossover effects of work-family conflict on job satisfaction, relationship satisfaction, and mental health for individuals (actor effects) as well as their spouses/partners (partner effects) in dual-earning couples. We further contribute by assessing whether the results vary by gender and union type. Results suggest that among married couples, for job satisfaction, there are no gender differences in actor effects (but gender di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(55 citation statements)
references
References 128 publications
(221 reference statements)
6
49
0
Order By: Relevance
“…While similar patterns for women and men were found in the relationship between satisfaction with family life and overall life satisfaction, different gender patterns may exist in the relationship between job satisfaction and overall life satisfaction as well as between satisfaction with food-related and life satisfaction in dual-earner couples. Therefore, our results are consistent with the findings reported by Yucel and Latshaw [ 73 ] in that gender differences in spillover and crossover relationships are associated with the variables under study. In the present study, the different gender patterns in the job and food domain are partially related to traditional gender roles, as we discuss below.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…While similar patterns for women and men were found in the relationship between satisfaction with family life and overall life satisfaction, different gender patterns may exist in the relationship between job satisfaction and overall life satisfaction as well as between satisfaction with food-related and life satisfaction in dual-earner couples. Therefore, our results are consistent with the findings reported by Yucel and Latshaw [ 73 ] in that gender differences in spillover and crossover relationships are associated with the variables under study. In the present study, the different gender patterns in the job and food domain are partially related to traditional gender roles, as we discuss below.…”
Section: Discussionsupporting
confidence: 93%
“…In summary, while some studies have found gender differences in spillover and crossover effects in couples [ 37 , 71 ], others report the opposite [ 26 , 72 ] or mixed results [ 73 ]. Two considerations are made here to begin to make sense of these inconsistent findings.…”
Section: Introductionmentioning
confidence: 99%
“…Challenges with time management raise the possibility that family transitions are more stressful for adults with ADHD when also managing a full-time job for the first time. Moreover, adults with ADHD may be especially prone to the “spillover” of stress from work to their family relationships, with implications for depressive symptoms (Yucel and Latshaw forthcoming).…”
Section: Discussionmentioning
confidence: 99%
“…Men and women's work and family careers are coupled, and they negotiate between these two spheres within the context of their relationship. Stressors relating to couples' work-family conflict and family-work conflict influence physical and mental health and are related to lower levels of marital satisfaction (Schieman et al, 2009;Yucel, 2017;Yucel & Latshaw, 2020). And mismatches in desired and actual work roles are likely to result in stress and negative health and mental health outcomes that affect other family members (Kalleberg, 2008).…”
Section: Linked Lives and Farming Work Arrangementsmentioning
confidence: 99%